2008
DOI: 10.1021/cm0714741
|View full text |Cite
|
Sign up to set email alerts
|

Novel Two-Step Method for Synthesis of High-Density Nanocrystalline Diamond Fibers

Abstract: We report a novel two-step method for the fabrication of high-density nanocrystalline diamond (NCD) fibers with lengths of 50-100 µm and diameters of 1-5 µm. This method includes the synthesis of templates (silica (a-SiO 2 ) nanofibers) by a conventional vapor-liquid-solid method and the conformal coating of the nanofibers with 15-20 nm sized NCD grains by a microwave plasma enhanced chemical vapor deposition technique in hydrogen-deficient conditions. A detailed microstructural analysis was performed to probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…This method includes the synthesis of templates (silica (a-SiO 2 ) nanofibers) by a conventional vapor-liquid-solid method and the conformal coating of the nanofibers with 15-20 nm sized nanocrystalline diamond (NCD) grains by microwave plasma enhanced chemical vapor deposition under hydrogen-deficient conditions. [93][94][95] The asprepared diamond nanowires showed good electron field emission properties. [94,95] Furthermore, our research group also reported a hot-filament chemical vapor deposition method using a Si nanowire template for the fabrication of arrays of boron-doped diamond nanowires and a 2D network of diamond nanowires.…”
Section: Cvd With Nanowire Templates For Diamond Nanowiresmentioning
confidence: 96%
“…This method includes the synthesis of templates (silica (a-SiO 2 ) nanofibers) by a conventional vapor-liquid-solid method and the conformal coating of the nanofibers with 15-20 nm sized nanocrystalline diamond (NCD) grains by microwave plasma enhanced chemical vapor deposition under hydrogen-deficient conditions. [93][94][95] The asprepared diamond nanowires showed good electron field emission properties. [94,95] Furthermore, our research group also reported a hot-filament chemical vapor deposition method using a Si nanowire template for the fabrication of arrays of boron-doped diamond nanowires and a 2D network of diamond nanowires.…”
Section: Cvd With Nanowire Templates For Diamond Nanowiresmentioning
confidence: 96%
“…The possibility of deposition of layered microdiamond coatings onto tungsten wires by the CVD method was demonstrated for the first time by May et al [62]. Afterward, many others reported successful the coating of microdiamond onto a variety of substrate wires including silicon carbide, copper, [66][67][68]. The as-prepared diamond nanowires showed good electron field emission properties [67,68].…”
Section: Nanowires-templated Cvd For Diamond Nanowiresmentioning
confidence: 99%
“…[85][86][87][88] Gasphase-Flüssigkeit-Feststoff-Verfahren und konformes Überziehen der Nanofasern mit 15-20 nm großen nanokristallinen Diamantkçrnern (NCD) durch Mikrowellenplasma-verstärkte chemische Gasphasenabscheidung unter wasserstoffarmen Bedingungen. [93][94][95] Die erhaltenen Diamant-Nanodrähte zeigten gute Elektronen-Feldemissionseigenschaften. [94,95] Unsere Arbeitsgruppe beschrieb ein Verfahren der chemischen Heißfilament-Gasphasenabscheidung mit Si-Nanodrahttemplaten zum Herstellen Bordotierter Diamant-Nanodrahtfelder und 2D-Diamant-Nanodrahtnetzwerke.…”
Section: Templatgestütztes Cvd-verfahrenunclassified